The past, present and future of research on judgment and decision making in sport. (May 2019) - Raab, Markus; Bar-Eli, Michael; Plessner, Henning; Araújo, Duarte
Abstract: Objectives: The study of judgment and decision-making in sports is at least as old as the anniversary of FEPSAC we celebrate with this special issue. It seems therefore appropriate to look into the past, present and future of this topic. Design: For the past, a focus of the review is relating the European perspective of the co-authors into a larger frame of areas in judgment and decision making within the last 50 years and beyond. Method/Results/Conclusions: For the present, scientific current developments will be structured as judgments from the most influential perspectives such as the economical, social cognition, ecological dynamics or cognitive approaches illustrating some milestones in research on judgment and decision-making in sports of today. For the future, potentials of the field will be structured based on theory, methodology and practical applications showcasing challenges for the next decades of research ahead of us. Highlights: Economical, social cognition, ecological dynamics and cognitive perspectives of judgment and decision making (JDM) in sports. Citation-network description of the four perspectives are provided. Future research proposals for JMD in sports are discussed.